Cultural, forage, medicinal and potential applications of Combretum collinum Fresen. (family Combretaceae) - Maroyi, Alfred (Ethnobotany Research and Applications, 2025)
Background: Ethnobotany is a relatively underdeveloped discipline in tropical Africa, and little attention has been paid to the traditional uses and the potential applications of indigenous plant species. This study was aimed at reviewing the cultural, forage, medicinal and potential applications of Combretum collinum Fresen., a shrub or small tree indigenous to several countries in tropical Africa. Methods: Literature on cultural, forage and medicinal uses of C. collinum was obtained from multiple internet sources such as Web of Science, Scopus®, SpringerLink®, Google Scholar, SciELO, PubMed® and ScienceDirect®. Complementary information was gathered from pre-electronic sources which included book chapters, books, scientific reports and journal articles obtained from the University library. Results: Historically, C. collinum was valued for forage, medicinal and cultural purposes, and as a food plant of minor importance. Literature studies showed that C. collinum is used as ethnoveterinary medicine, and traditional medicine against respiratory infections, gastro-intestinal problems, malaria, evil spirits, fatigue, rheumatism, epilepsy, haemorrhoids, pain, infertility in women, wounds, snake bites and skin disorders. Phytochemical research identified alkanes, alkaloids, bibenzyls, fatty acids, flavonoids, phenanthrenes, phenols, phytosterols, stilbenoids, tannins and terpenoids. Phytochemical compounds and crude extracts of C. collinum demonstrated anthelmintic, antibacterial, antifungal, anti-inflammatory, antioxidant, antiplasmodial, antiproliferative, antityrosinase, larvicidal and cytotoxicity activities. Conclusion: In the last few decades, tropical Africa has seen changes in access to modern healthcare, and these changes in the socio-cultural aspects have severely affected the indigenous knowledge of useful plant species such as C. collinum. Therefore, results of the current study stimulate scientific documentation of indigenous knowledge, application and beneficiation of this knowledge as a strategy of supporting sustainable utilization of plant species in tropical Africa. Keywords: Combretaceae, Combretum collinum, Indigenous knowledge, Materia medica, Traditional medicine